Design of dualband antenna for RFID applications - N. M. Sahar; M.T. Islam; N. Misran (International Journal of Electrical and Computer Engineering (IJECE), 2019)
This paper focuses on the design and fabrication of dual band antenna for UHF RFID and ISM RFID applications. The U-shaped patch loaded with dipole is introduced and investigated. The antenna can be performed dual-band frequencies at 0.915 GHz and 2.4 GHz required in RFID applications with reflection coefficient is less than -10 dB. The lower band can be varied by adjusting both dipole arms length and upper band is tuned by U-shaped patches. The gains of the design with a size 130   45  1.6 mm3  are performed 1.89 dB and 3.65 dB for single and dual band respectively. This compact and low cost dual band antenna also performed total efficiency greater than 80%. The design methodology and antenna measurement results are both presented and discussed in this letter.